Collaboratie in Vlaanderen : vergeten en vergeven? - Corijn, Eric; Deneckere, Gita; De Wever, Bruno; Grauwels, Anne (Antwerpen: Manteau, 2002)
"onder redactie van Eric Corijn ; Gita Deneckere, Bruno De Wever, Anne Grauwels et al."